2021
DOI: 10.3928/01484834-20210322-05
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Learning Characteristics of Nursing Students: A Literature Review

Abstract: Background: Research findings have revealed that some students are not prepared to face the challenges associated with online learning, and attrition rates have been found to be a major concern. This review aimed to investigate the learning characteristics nursing students need before enrolling in online learning to ensure success. Method: Electronic databases were searched to investigate the learning characteristics of students for the literature revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…4 When searching through various school and degree options and trying to decipher the unfamiliar language of school catalogs, students may feel these are unachievable time-consuming tasks to accomplish. Cadet 5 reported that when nursing students are not prepared for online learning in particular, attrition rates increase. To combat this issue, students need to consider components such as a plan of study, student services, and clinical site placements and review each school' s educational options (in-person, online, or a hybrid) to determine which will best fit their lifestyle.…”
mentioning
confidence: 99%
“…4 When searching through various school and degree options and trying to decipher the unfamiliar language of school catalogs, students may feel these are unachievable time-consuming tasks to accomplish. Cadet 5 reported that when nursing students are not prepared for online learning in particular, attrition rates increase. To combat this issue, students need to consider components such as a plan of study, student services, and clinical site placements and review each school' s educational options (in-person, online, or a hybrid) to determine which will best fit their lifestyle.…”
mentioning
confidence: 99%